The Adventure of Mat Kilau: Enhancing Listening Comprehension through an Interactive Computer Game - Munira Abd Rahman; Siti Hanisah Abdul Rahman; Noraini Md Said; Melor Md Yunus (Malaysia Journal of Invention and Innovation, 2023)
Globalisation and fast-growing information technology have strikingly changed the approaches to ESL teaching and learning in the past few decades. On account of the increasing demands of the 21st century, the awareness on the importance of listening skills, especially listening comprehension, has grown tremendously. This is due to the realisation that excellent listening comprehension enables learners to communicate effectively and meaningfully. However, in the Malaysian context, studies found that listening skills are still perceived as less important than other language skills. Therefore, this paper aims to fill the gap by developing ‘The Adventure of Mat Kilau’, an interactive computer game to enhance ESL learners’ listening comprehension. The game features a Malay hero ‘Mat Kilau’ as the main character and different tasks which need the players to listen to verbal instructions. This paper also describes the stages of the research which include the needs analysis, design, development, implementation, and evaluation. Based on the findings, it is concluded that this interactive game works as a fun, challenging, and motivating tool for lower primary ESL listening comprehension.